DINAMIKA BUDAYA, GOTONG ROYONG, DAN KERUKUNAN SOSIAL DALAM MASYARAKAT MULTIKULTURAL - Nurjannah, Anjeli Indayanti, Fadillah, Ratih Ramadhani, Amirah Nadia Kalila, Della Ramiyati (FKIP UMN ALWASHLIYAH, 2026)
Social and cultural change is an inseparable phenomenon in modern society. This article aims to analyze the dynamics of cultural traditions, the practice of mutual cooperation (gotong royong), and forms of social interaction within a multicultural society experiencing changes driven by economic factors, governmental structures, and the evolution of the times. The study employs a qualitative descriptive approach based on field research through interviews and social observations. The findings indicate that religious traditions remain a central pillar in maintaining cultural identity and social harmony, although traditional forms of gotong royong have declined and some of their functions have been replaced by formal governmental institutions. Cultural values are transmitted to younger generations through religious activities, youth organizations, and daily social interactions that emphasize tolerance. This article is expected to contribute to socio-cultural studies and serve as a reference for the development of programs aimed at strengthening social harmony. ↓ Keywords: culture, gotongyong, social harmony, multicultural society social change